Microbiological evaluation of certain fruits and vegetables marketed in the city of Kenitra-Morocco - Erahioui Rahma; Inekach Sultana; Jaber Hassna; Atfaoui Khadija; Rhaim Noureddine; Mennane Zakaria; Ouhssine Mohammed (E3S Web of Conferences, 2021)
Fruits and vegetables are essential for human health due to their nutritional qualities, but the consumption of raw foods leads to food safety problems as they are recognized as sources of transmission of infectious diseases. The objective of this work is to assess the microbiological quality of some fruits and vegetables marketed in the Kenitra city. The samples were purchased at the fruit and vegetable markets during the period from April to July 2018.The detection of microorganisms in the samples requires several steps which are weighing, dilution, isolation, enumeration and 'identification. The results of the microbiological analysis of fruits and vegetables studied show significant concentrations of the total aerobic mesophilic flora varies between 2.25 and 8.48 log10 CFU / ml, Concerning total coliforms the contamination rates vary between 1.92 and 8.42 log10UFC / ml, as well as the presence of fecal coliforms between 1.13 and 8.05 log10UFC / ml, in the same samples analyzed, strains such as: Escherichia coli, staphylococcus aureus and a total absence of salmonella and shegilla. In order to improve the safety and hygienic quality of fruits and vegetables, the application of good hygienic practices as well as continuous microbial quality control is necessary to protect the health of consumers.